Patient and Caregiver Perspectives on Communication Quality in Tele-Palliative Care - Julia I. Bandini; Elaine Li; Dio Kavalieratos; Natalie C. Ernecoff; Kimberly Curseen; Jordan Harrison (Journal of Palliative Medicine, 2026)
Background: Tele-palliative care has become a well-established practice following its rapid expansion in the outpatient setting during the COVID-19 pandemic. Despite sustained integration of tele-palliative care, questions remain about patients’ and family caregivers’ experiences with it and its potential impact on the quality of communication during palliative care visits. Objective: To qualitatively explore patient and family caregiver experiences with telehealth and in-person visits for outpatient palliative care, including preferences related to mode of care and any perceived differences in communication quality by mode in a post-pandemic context. Methods: We conducted semistructured interviews with 26 participants (15 patients and 11 family caregivers) receiving outpatient palliative care at one academic medical center in the southern United States. Results: Three themes emerged: (1) participants weighed convenience, symptom burden, and visit reason in choosing mode of care; (2) opinions differed on the authenticity of communication via telehealth; and (3) comfort and privacy shaped communication quality. Some patients and family caregivers perceived communication via telehealth as comparable to in-person care, while others felt in-person visits allowed for more authentic interactions. Many found that the convenience of telehealth outweighed any perceived differences in communication quality. In addition, some patients noted that without the option for telehealth, the benefits of an in-person palliative care visit may not have outweighed the travel burden. Conclusions: Telehealth can support high-quality communication and offer meaningful access for outpatient palliative care. A hybrid model of care provides a person-centered approach to meet the needs of patients with serious illness and their family caregivers.